Utilization Patterns and Patient Outcomes Associated with Use of Rescue Therapies in Acute Lung Injury - Walkey, Allan J. (2011)
OBJECTIVE: To investigate the practice patterns and clinical outcomes associated with use of rescue therapies in patients with acute lung injury (ALI). DESIGN: Secondary analysis of multi-center, randomized-controlled trial data from the National Heart, Lung and Blood Institute (NHLBI) ARDS Clinical Trials Network (ARDSNet). SETTING: Intensive care units of ARDSNet centers across the United States. PATIENTS: Subjects enrolled in 6 ARDSNet trials occurring between1996–2005. INTERVENTIONS: None MEASUREMENTS AND MAIN RESULTS: 166/2632(6.3%) of subjects received rescue therapy, defined as prone positioning [97/166 (58%)], inhaled vasodilators [47/166 (28%)], high frequency ventilation (HFV) [12/166 (7%)] or extracorporeal membrane oxygenation (ECMO) [10/166 (6%)]. Use of inhaled vasodilators increased while use of prone position decreased over time (p for trend = 0.04 and 0.0013, respectively). Multivariate predictors for use of rescue therapy included age [odds ratio (OR) per 10 years, (95% confidence intervals): 0.88, (0.78–0.99), p=0.049], positive end expiratory pressure (PEEP) [OR per 5 cm H2O increase 1.33, (1.05–1.69), p=0.019], PaO(2)/FiO(2) [OR per 5 increase: 0.98, (0.96–0.99), p=0.017], peak airway pressure [OR per 5cm H(2)O increase: 1.11, (1.001–1.237), p=0.047], and study order [OR per subsequent ARDSNet study: 1.21, (1.03–1.41), p=0.02]. Cox proportional hazards analysis of propensity score-matched subjects showed no difference in survival for those who received rescue therapy versus those that did not [Hazard ratio (HR) for death after rescue therapy or index date 1.10, (0.67–1.78), p=0.72]. No differences in survival were found between those who received prone positioning versus inhaled vasodilators [propensity score-adjusted HR for prone 0.87 (0.86–2.10), p=0.76]. CONCLUSIONS: Rescue therapies are utilized in younger patients with more severe oxygenation deficits. Patterns of rescue therapy utilization appear to be changing over time. Within the limits of an observational study design, we did not find evidence of a survival benefit with use of rescue therapies in ALI.